High flame-retardant low-density PVC composite foamed board and preparation process thereof

CN122917460APending Publication Date: 2026-10-16LINYI HUALI JIECHENG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611195009.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

轻质与阻燃的兼顾在原理上构成尖锐的工艺矛盾:减少阻燃剂则阻燃不足,增加阻燃剂则密度升高且泡孔结构崩坏,力学性能严重恶化

Benefits of technology

首次将包覆焦磷酸哌嗪硼酸盐微胶囊用于PVC发泡体系。该微胶囊外壳显著提升了芯材的热稳定性和与PVC基体的相容性,且燃烧时壳层降解形成纳米二氧化硅,与芯材释放的磷酸、硼酸协同作用,在基体表面构建连续致密的硅-磷-硼-碳杂化层,高效阻隔热量与氧气传递。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of high flame-retardant low-density PVC composite foamed sheet and preparation process thereof, belong to PVC plate technical field.The PVC composite foamed sheet of the application includes the following raw materials: polyvinyl chloride resin, foaming agent, foaming stabilizer, calcium-zinc composite heat stabilizer, processing aid, light calcium carbonate, lubricant, modified phosphorus-silicon flame-retardant microcapsule, phytate bacteria furfuryl porous carbon.The application innovatively adds modified phosphorus-silicon flame-retardant microcapsule and phytate bacteria furfuryl porous carbon, and the modified phosphorus-silicon flame-retardant microcapsule and phytate porous carbon form a significant synergistic intumescent flame-retardant circuit during combustion, and the two compounds realize efficient synergy: porous carbon as a carbon layer skeleton carrier, together with the various flame-retardant elements released by microcapsule, jointly promote the formation of a solid, intumescent composite barrier layer, which greatly improves the flame-retardant performance of PVC plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of PVC sheet technology, specifically relating to a high flame-retardant low-density PVC composite foamed board and its preparation process. Background Technology

[0002] PVC foam boards are widely used in building decoration, advertising signage, and other fields due to their lightweight and easy processing. However, increasingly stringent requirements are being placed on their flame retardancy, safety, and low density. Achieving a balance between high flame retardancy and low density is a recognized extreme technical challenge in the industry.

[0003] Flame retardant modification and foaming processes are inherently conflicting. To achieve a certain flame retardant rating, large amounts of flame retardants are often required. However, conventional inorganic flame retardants such as aluminum hydroxide and magnesium hydroxide often require tens to hundreds of parts, causing a sharp increase in the density of the board and negating the lightweight advantage of foamed boards. While traditional halogenated flame retardants are highly efficient, they release large amounts of toxic fumes and corrosive gases during combustion, facing stringent environmental and safety regulations, thus narrowing their application channels.

[0004] While intumescent flame retardants are considered an alternative to halogen-free processes, their application in PVC foaming systems presents significant challenges. Common acid-carbon-gas source combinations have poor compatibility with the PVC matrix, severely degrading melt strength and causing cell merging and collapse during foaming. This prevents the formation of a uniform and dense cell structure, hindering effective reduction in sheet density. Tensile strength and elongation at break also deteriorate rapidly, transforming the material from tough to brittle, rendering it impractical. Furthermore, conventional phosphorus-based flame retardants lack sufficient thermal stability at PVC processing temperatures, leading to premature decomposition. This not only weakens the flame-retardant effect but also causes processing instability and product discoloration. Carbon-containing carbon source components often lack efficient synergy with flame-retardant elements; when used alone, they form a loose, cracked char layer, failing to establish a sufficiently dense thermal and oxygen barrier, and thus unable to raise the limiting oxygen index to a high level.

[0005] Furthermore, to achieve both lightweight properties and high flame retardancy, the porous structure within the foam board provides channels for the propagation of flames and combustible gases, and facilitates oxygen penetration, further complicating the already challenging flame retardancy requirements. The balance between lightweight and flame retardancy presents a sharp technological contradiction: reducing the flame retardant results in insufficient flame retardancy, while increasing it increases density and disrupts the cell structure, severely deteriorating mechanical properties. Current technology has consistently failed to achieve high-quality foamed materials with fine, uniform cells and low apparent density at relatively low flame retardant dosages. This situation constitutes an extreme bottleneck in the upgrading of PVC foam boards to high performance, urgently requiring a breakthrough to overcome the long-standing impasse of reconciling flame retardancy, density, and mechanical properties. Summary of the Invention

[0006] The purpose of this invention is to provide a high flame retardant, low-density PVC composite foam board.

[0007] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows: A high flame-retardant, low-density PVC composite foam board comprises the following raw materials in parts by weight: 100 parts polyvinyl chloride resin, 1-3 parts foaming agent, 5-15 parts foaming stabilizer, 2-5 parts calcium-zinc composite heat stabilizer, 5-10 parts processing aid, 10-20 parts light calcium carbonate, 0.5-2 parts lubricant, 5-15 parts modified phosphorus-silicon flame-retardant microcapsules, and 3-10 parts phytic acid bacteria bran-based porous carbon.

[0008] Furthermore, the preparation method of the modified phosphorus silicon flame-retardant microcapsules is as follows: (1) Disperse piperazine pyrophosphate and boric acid in deionized water at a mass ratio of 1:0.3-0.8 to prepare a suspension, stir at 80℃ for 2 hours, and spray dry to obtain core powder; (2) Mix the above core powder with deionized water at a mass ratio of 1:10, then add 2% of Tween-80 by mass of the core powder, and ultrasonically disperse the mixture at room temperature for 30 minutes to form a suspension. Adjust the pH to 8.0-8.5. (3) Place the system in a 45°C water bath, take 20% of the core powder mass of vinyltriethoxysilane, and add an equal mass of anhydrous ethanol to mix and obtain a mixture. Add the mixture dropwise to the suspension in step 2, stir at a constant temperature for 5.5 h, let stand for 2 h, centrifuge to separate the solid product, wash with deionized water and anhydrous ethanol 2-3 times in sequence, and vacuum dry to constant weight to obtain modified phosphorus silicon flame retardant microcapsules.

[0009] Furthermore, the total mass ratio of piperazine pyrophosphate and boric acid to deionized water is 1:4.

[0010] Furthermore, the method for preparing the phytic acid-oxidizing bacteria bran-based porous carbon is as follows: S1: The waste mushroom residue was dried and pulverized. The dried mushroom residue powder was weighed according to a mass ratio of 1:2 to solid KOH and a 20wt% KOH aqueous solution was prepared to impregnate the dried mushroom residue powder for 12 hours and then dried. The above mixture was carbonized for 1.5 hours at 800℃ under nitrogen protection at a temperature of 5℃ / min. The product was soaked in 0.1 mol / L hydrochloric acid, washed with deionized water until neutral, and dried to obtain mushroom residue-based porous carbon. S2: Disperse porous carbon in a 15-30wt% phytic acid aqueous solution with a mass-to-volume ratio of 1g:10mL. Stir in a water bath at 60℃ for 4h. After filtering the reaction solution, wash the solid product with deionized water, dry it under vacuum at 80℃, and bake it at 120℃ for 4h to obtain phytic acid-modified bran-based porous carbon.

[0011] Furthermore, the foaming agent is azodicarbonamide and sodium bicarbonate, with a mass ratio of 1:0.8.

[0012] Furthermore, the foaming stabilizer is an acrylate foaming regulator, and the processing aid is an acrylate copolymer.

[0013] Furthermore, the lubricant is polyethylene wax and stearic acid, with a mass ratio of 1:1.

[0014] A preparation process for a high flame-retardant, low-density PVC composite foam board includes the following steps: (1) First, prepare modified phosphorus-silicon flame-retardant microcapsules and phytic acid bacteria bran-based porous carbon. Add the weighed PVC resin, calcium-zinc composite stabilizer, processing aid, foaming stabilizer and lubricant to the mixer and start stirring at 200 rpm. When the material temperature rises to 60-70℃, add light calcium carbonate, modified phosphorus-silicon flame-retardant microcapsules and phytic acid bacteria bran-based porous carbon, and stir at a rate of 400-600 rpm. When the temperature of the mixture rises to 100-110℃, add the pre-mixed foaming agent and stir at a rate of 100 rpm for 1-2 minutes. Discharge the mixture into a cold mixer and stir and cool until the material temperature is <40℃ to obtain a dry powder premix. (2) Add the cooled premixed material into the hopper of the conical twin-screw extruder, and set the temperature of each section of the extruder as follows: feeding section 150-160℃, compression section 160-170℃, metering section 170-180℃, die head temperature 165-175℃, and screw speed controlled at 15-25r / min. (3) The material is plasticized and melted in the extruder. After the melt is extruded through the die, it is cooled and shaped in the shaping device. The board is then pulled and cut to a fixed length to obtain a high flame retardant low density PVC composite foam board.

[0015] All raw materials used in this invention are commercially available.

[0016] Beneficial effects For the first time, piperazine pyrophosphate borate microcapsules have been used in a PVC foaming system. The shell of these microcapsules significantly improves the thermal stability of the core material and its compatibility with the PVC matrix. During combustion, the shell degrades to form nano-silica, which, in synergy with the phosphoric acid and boric acid released from the core material, constructs a continuous and dense silicon-phosphorus-boron-carbon hybrid layer on the matrix surface, effectively blocking heat and oxygen transfer.

[0017] For the first time, phytic acid-modified bacterial bran-based porous carbon has been introduced into foamed boards. This porous carbon has a hierarchical pore structure, which can serve as a highly efficient foaming nucleating agent, promoting the formation of fine and uniform pores and effectively reducing the density of the board. When the phytic acid grafted on its surface is heated, it releases phosphoric acid, which acts as an acid source and synergistically forms carbon with the carbon source of the porous carbon itself, thus realizing the high-value utilization of agricultural waste bacterial bran.

[0018] Modified microcapsules and phytic acid-modified porous carbon form a significant synergistic expansion flame-retardant circuit during combustion. The combination of the two achieves high efficiency and synergy: porous carbon, as the carbon layer skeleton carrier, works with various flame-retardant elements released by the microcapsules to promote the formation of a strong, expanding composite barrier layer, thereby greatly improving the flame-retardant performance of PVC sheets.

[0019] The PVC foam board preparation process of this invention is simple, and it can directly use existing PVC foam board extrusion equipment without major modifications, making it easy to promote industrialization. Detailed Implementation

[0020] The technical solution of the present invention will be further described below with reference to specific embodiments, but it is not limited thereto.

[0021] Example 1 A high flame-retardant, low-density PVC composite foam board comprises the following raw materials in parts by weight: 100 parts of polyvinyl chloride resin, 1 part of foaming agent, 5 parts of foaming stabilizer, 2 parts of calcium-zinc composite heat stabilizer, 5 parts of processing aid, 10 parts of light calcium carbonate, 0.5 parts of lubricant, 5 parts of modified phosphorus-silicon flame-retardant microcapsules, and 3 parts of phytic acid bacteria bran-based porous carbon.

[0022] The preparation method of the modified phosphorus silicon flame retardant microcapsules is as follows: (1) Piperazine pyrophosphate and boric acid were dispersed in deionized water at a mass ratio of 1:0.3 to prepare a suspension. The suspension was stirred at 80°C for 2 hours and then spray-dried to obtain core powder. (2) Mix the above core powder with deionized water at a mass ratio of 1:10, then add 2% of Tween-80 by mass of the core powder, and ultrasonically disperse the mixture at room temperature for 30 minutes to form a suspension. Adjust the pH to 8.0-8.5. (3) Place the system in a 45°C water bath, take 20% of the core powder mass of vinyltriethoxysilane, and add an equal mass of anhydrous ethanol to mix and obtain a mixture. Add the mixture dropwise to the suspension in step 2, stir at a constant temperature for 5.5 h, let stand for 2 h, centrifuge to separate the solid product, wash twice with deionized water and anhydrous ethanol, and vacuum dry to constant weight to obtain modified phosphorus silicon flame retardant microcapsules.

[0023] The total mass ratio of piperazine pyrophosphate and boric acid to deionized water is 1:4.

[0024] The method for preparing the phytic acid-oxidizing bacteria bran-based porous carbon is as follows: S1: The waste mushroom residue was dried and pulverized. The dried mushroom residue powder was weighed according to a mass ratio of 1:2 to solid KOH and a 20wt% KOH aqueous solution was prepared to impregnate the dried mushroom residue powder for 12 hours and then dried. The above mixture was carbonized for 1.5 hours at 800℃ under nitrogen protection at a temperature of 5℃ / min. The product was soaked in 0.1 mol / L hydrochloric acid, washed with deionized water until neutral, and dried to obtain mushroom residue-based porous carbon. S2: Disperse porous carbon in a 15wt% phytic acid aqueous solution with a mass-to-volume ratio of 1g:10mL. Stir in a water bath at 60℃ for 4h. After filtering the reaction solution, wash the solid product with deionized water, dry it under vacuum at 80℃, and bake it at 120℃ for 4h to obtain phytic acid-modified bran-based porous carbon.

[0025] The foaming agent is azodicarbonamide and sodium bicarbonate, with a mass ratio of 1:0.8.

[0026] The foaming stabilizer is an acrylate foaming regulator, and the processing aid is an acrylate copolymer.

[0027] The lubricant is polyethylene wax and stearic acid, with a mass ratio of 1:1.

[0028] A preparation process for a high flame-retardant, low-density PVC composite foam board includes the following steps: (1) First, prepare modified phosphorus silicon flame retardant microcapsules and phytic acid bacteria bran-based porous carbon. Add the weighed PVC resin, calcium zinc composite stabilizer, processing aid, foaming stabilizer and lubricant to the mixer and start stirring at 200 rpm. When the material temperature rises to 60°C, add light calcium carbonate, modified phosphorus silicon flame retardant microcapsules and phytic acid bacteria bran-based porous carbon and stir at 400 rpm. When the temperature of the mixture rises to 100°C, add the pre-mixed foaming agent and stir at 100 rpm for 1-2 minutes. Discharge the mixture into the cold mixer and stir and cool until the material temperature is <40°C to obtain dry powder premix. (2) Add the cooled premixed material into the hopper of the conical twin-screw extruder, and set the temperature of each section of the extruder as follows: feeding section 150℃, compression section 160℃, metering section 170℃, die head temperature 165℃, and screw speed controlled at 15r / min. (3) The material is plasticized and melted in the extruder. After the melt is extruded through the die, it is cooled and shaped in the shaping device. The board is then pulled and cut to a fixed length to obtain a high flame retardant low density PVC composite foam board.

[0029] Example 2 A high flame-retardant, low-density PVC composite foam board comprises the following raw materials in parts by weight: 100 parts polyvinyl chloride resin, 2 parts foaming agent, 10 parts foaming stabilizer, 3 parts calcium-zinc composite heat stabilizer, 8 parts processing aid, 15 parts light calcium carbonate, 1.2 parts lubricant, 10 parts modified phosphorus-silicon flame-retardant microcapsules, and 6 parts phytic acid bacteria bran-based porous carbon.

[0030] The preparation method of the modified phosphorus silicon flame retardant microcapsules is as follows: (1) Disperse piperazine pyrophosphate and boric acid in deionized water at a mass ratio of 1:0.5 to prepare a suspension, stir at 80°C for 2 hours, and spray dry to obtain core powder; (2) Mix the above core powder with deionized water at a mass ratio of 1:10, then add 2% of Tween-80 by mass of the core powder, and ultrasonically disperse the mixture at room temperature for 30 minutes to form a suspension. Adjust the pH to 8.0-8.5. (3) Place the system in a 45°C water bath, take 20% of the core powder mass of vinyltriethoxysilane, and add an equal mass of anhydrous ethanol to mix and obtain a mixture. Add the mixture dropwise to the suspension in step 2, stir at a constant temperature for 5.5 h, let stand for 2 h, centrifuge to separate the solid product, wash with deionized water and anhydrous ethanol three times in sequence, and vacuum dry to constant weight to obtain modified phosphorus silicon flame retardant microcapsules.

[0031] The total mass ratio of piperazine pyrophosphate and boric acid to deionized water is 1:4.

[0032] The method for preparing the phytic acid-oxidizing bacteria bran-based porous carbon is as follows: S1: The waste mushroom residue was dried and pulverized. The dried mushroom residue powder was weighed according to a mass ratio of 1:2 to solid KOH and a 20wt% KOH aqueous solution was prepared to impregnate the dried mushroom residue powder for 12 hours and then dried. The above mixture was carbonized for 1.5 hours at 800℃ under nitrogen protection at a temperature of 5℃ / min. The product was soaked in 0.1 mol / L hydrochloric acid, washed with deionized water until neutral, and dried to obtain mushroom residue-based porous carbon. S2: Porous carbon was dispersed in a 22wt% phytic acid aqueous solution with a mass-to-volume ratio of 1g:10mL. The mixture was stirred in a water bath at 60℃ for 4h. After filtration, the solid product was washed with deionized water, dried under vacuum at 80℃, and baked at 120℃ for 4h to obtain phytic acid-modified bran-based porous carbon.

[0033] The foaming agent is azodicarbonamide and sodium bicarbonate, with a mass ratio of 1:0.8.

[0034] The foaming stabilizer is an acrylate foaming regulator, and the processing aid is an acrylate copolymer.

[0035] The lubricant is polyethylene wax and stearic acid, with a mass ratio of 1:1.

[0036] A preparation process for a high flame-retardant, low-density PVC composite foam board includes the following steps: (1) First, prepare modified phosphorus silicon flame retardant microcapsules and phytic acid bacteria bran-based porous carbon. Add the weighed PVC resin, calcium zinc composite stabilizer, processing aid, foaming stabilizer and lubricant to the mixer and start stirring at 200 rpm. When the material temperature rises to 65°C, add light calcium carbonate, modified phosphorus silicon flame retardant microcapsules and phytic acid bacteria bran-based porous carbon and stir at 500 rpm. When the temperature of the mixture rises to 105°C, add the pre-mixed foaming agent and stir at 100 rpm for 1-2 minutes. Discharge the mixture into the cold mixer and stir and cool until the material temperature is <40°C to obtain dry powder premix. (2) Add the cooled premixed material into the hopper of the conical twin-screw extruder, and set the temperature of each section of the extruder as follows: feeding section 155℃, compression section 165℃, metering section 175℃, die head temperature 170℃, and screw speed controlled at 20r / min. (3) The material is plasticized and melted in the extruder. After the melt is extruded through the die, it is cooled and shaped in the shaping device. The board is then pulled and cut to a fixed length to obtain a high flame retardant low density PVC composite foam board.

[0037] Example 3 A high flame-retardant, low-density PVC composite foam board comprises the following raw materials in parts by weight: 100 parts of polyvinyl chloride resin, 3 parts of foaming agent, 15 parts of foaming stabilizer, 5 parts of calcium-zinc composite heat stabilizer, 10 parts of processing aid, 20 parts of light calcium carbonate, 2 parts of lubricant, 15 parts of modified phosphorus-silicon flame-retardant microcapsules, and 10 parts of phytic acid-modified bran-based porous carbon.

[0038] The preparation method of the modified phosphorus silicon flame retardant microcapsules is as follows: (1) Disperse piperazine pyrophosphate and boric acid in deionized water at a mass ratio of 1:0.8 to prepare a suspension, stir at 80°C for 2 hours, and spray dry to obtain core powder; (2) Mix the above core powder with deionized water at a mass ratio of 1:10, then add 2% of Tween-80 by mass of the core powder, and ultrasonically disperse the mixture at room temperature for 30 minutes to form a suspension. Adjust the pH to 8.0-8.5. (3) Place the system in a 45°C water bath, take 20% of the core powder mass of vinyltriethoxysilane, and add an equal mass of anhydrous ethanol to mix and obtain a mixture. Add the mixture dropwise to the suspension in step 2, stir at a constant temperature for 5.5 h, let stand for 2 h, centrifuge to separate the solid product, wash with deionized water and anhydrous ethanol 2-3 times in sequence, and vacuum dry to constant weight to obtain modified phosphorus silicon flame retardant microcapsules.

[0039] The total mass ratio of piperazine pyrophosphate and boric acid to deionized water is 1:4.

[0040] The method for preparing the phytic acid-oxidizing bacteria bran-based porous carbon is as follows: S1: The waste mushroom residue was dried and pulverized. The dried mushroom residue powder was weighed according to a mass ratio of 1:2 to solid KOH and a 20wt% KOH aqueous solution was prepared to impregnate the dried mushroom residue powder for 12 hours and then dried. The above mixture was carbonized for 1.5 hours at 800℃ under nitrogen protection at a temperature of 5℃ / min. The product was soaked in 0.1 mol / L hydrochloric acid, washed with deionized water until neutral, and dried to obtain mushroom residue-based porous carbon. S2: Disperse porous carbon in a 30wt% phytic acid aqueous solution with a mass-to-volume ratio of 1g:10mL. Stir in a water bath at 60℃ for 4h. After filtering the reaction solution, wash the solid product with deionized water, dry it under vacuum at 80℃, and bake it at 120℃ for 4h to obtain phytic acid-modified bran-based porous carbon.

[0041] The foaming agent is azodicarbonamide and sodium bicarbonate, with a mass ratio of 1:0.8.

[0042] The foaming stabilizer is an acrylate foaming regulator, and the processing aid is an acrylate copolymer.

[0043] The lubricant is polyethylene wax and stearic acid, with a mass ratio of 1:1.

[0044] A preparation process for a high flame-retardant, low-density PVC composite foam board includes the following steps: (1) First, prepare modified phosphorus silicon flame retardant microcapsules and phytic acid bacteria bran-based porous carbon. Add the weighed PVC resin, calcium zinc composite stabilizer, processing aid, foaming stabilizer and lubricant to the mixer and start stirring at 200 rpm. When the material temperature rises to 70°C, add light calcium carbonate, modified phosphorus silicon flame retardant microcapsules and phytic acid bacteria bran-based porous carbon and stir at 600 rpm. When the temperature of the mixture rises to 110°C, add the pre-mixed foaming agent and stir at 100 rpm for 1-2 minutes. Discharge the mixture into the cold mixer and stir and cool until the material temperature is <40°C to obtain dry powder premix. (2) Add the cooled premixed material into the hopper of the conical twin-screw extruder, and set the temperature of each section of the extruder as follows: feeding section 160℃, compression section 170℃, metering section 180℃, die head temperature 175℃, and screw speed controlled at 25r / min. (3) The material is plasticized and melted in the extruder. After the melt is extruded through the die, it is cooled and shaped in the shaping device. The board is then pulled and cut to a fixed length to obtain a high flame retardant low density PVC composite foam board.

[0045] Comparative Example 1 Compared with Example 3, this comparative example is identical to Example 3 except that no modified phosphorus silicon flame retardant microcapsules are added.

[0046] Comparative Example 2 Compared with Example 3, this comparative example is identical to Example 3 except that no phytic acid bacteria bran-based porous carbon is added.

[0047] Comparative Example 3 Compared with Example 3, this comparative example does not add modified phosphorus silicon flame retardant microcapsules, but only adds the same mass of the core powder obtained in step (1) of the preparation of modified phosphorus silicon flame retardant microcapsules. All other raw materials and steps are the same as in Example 3.

[0048] Performance testing PVC composite foam boards were prepared according to the components and steps of Examples 1-3 and Comparative Examples 1-3, and their flame retardancy, density and other indicators were measured. The limiting oxygen index was determined in accordance with GB / T 2406.2—2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test"; Density was determined according to GB / T 6343-2009 "Determination of Apparent Density of Foamed Plastics and Rubber". The test environment temperature was 23±2℃ and the humidity was (50±10)%. Tensile strength and elongation at break were determined in accordance with GB / T 1040.2-2006 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics" (referencing foamed board standard QB / T 2463.1); the test data are shown in Table 1.

[0049] Table 1 Performance indicators of PVC composite foamed boards in each treatment group As can be seen from the data in Table 1, the PVC sheets prepared by the present invention have high flame retardancy, and Example 3 has the lowest density.

[0050] Compared to Example 3, Comparative Example 1 did not add modified phosphorus-silicon flame-retardant microcapsules, retaining only phytic acid-modified bran-based porous carbon. However, the limiting oxygen index of Comparative Example 1 decreased significantly. This is because the lack of microcapsules to provide phosphorus, boron, and silicon sources makes it difficult to form a dense heat and oxygen barrier during combustion. In terms of density, Comparative Example 1 decreased to 483 kg / m³, a reduction of 34 kg / m³ compared to 517 kg / m³ in Example 3. This is because the microcapsule component, which has a higher density, was removed, and only porous carbon acted as a highly efficient nucleating agent, resulting in finer pores and a higher foaming ratio, leading to a lower apparent density. In terms of mechanical properties, the tensile strength decreased from 13.4 MPa to 10.1 MPa, and the elongation at break slightly decreased from 9.3% to 8.6%. The strength decreased significantly due to the loss of the reinforcing effect and interfacial compatibility improvement effect of the microcapsules. However, because the porous carbon can still uniformly create pores and passivate cracks, the toughness remained relatively good.

[0051] Compared to Example 3, Comparative Example 2 did not add phytic acid-oxidizing bacteria bran-based porous carbon, but only introduced modified phosphorus-silicon flame-retardant microcapsules. Compared to Example 3, the limiting oxygen index of Comparative Example 2 decreased from 38.2% to 33.4%, a decrease of 4.8 percentage points, indicating weakened flame retardancy. This suggests that the lack of porous carbon results in the loss of the efficient adsorption of combustible gases by the hierarchical porous structure and its role as a char source for synergistic char formation. The compactness and expansion effect of the microcapsules alone are not as good as the composite system. The density increased significantly from 517 kg / m³ to 590 kg / m³, an increase of 73 kg / m³. This is because without the hierarchical pore nucleation sites provided by porous carbon, the pores became larger and more uneven, leading to a decrease in the foaming ratio. The tensile strength decreased from 13.4 MPa to 11.5 MPa, a drop of 1.9 MPa, while the elongation at break dropped sharply from 9.3% to 5.8%, a decrease of 3.5 percentage points. This indicates that the lack of porous carbon not only weakens the interfacial reinforcement but also causes the material to lose the cell toughening mechanism, and the fracture behavior changes from toughness to brittleness.

[0052] Compared to Example 3, Comparative Example 3 used an equal mass of core powder (a mixture of piperazine pyrophosphate and borate, without silane coating) instead of the modified phosphosilicate flame-retardant microcapsules. Compared to Example 3, the limiting oxygen index of Comparative Example 3 decreased from 38.2% to 31.7%, a reduction of 6.5 percentage points, indicating a significantly worse flame-retardant effect. The uncoated core powder could not degrade through the shell to generate nano-silica during combustion, lacking silicon synergy, making it difficult to construct a complete silicon-phosphorus-boron-carbon hybrid ceramic carbon layer. Furthermore, the core material had poor thermal stability, partially decomposing prematurely, reducing the effective flame-retardant components. The density increased from 517 kg / m³ to 531 kg / m³, an increase of 14 kg / m³. This was because the core powder had poor compatibility with PVC, resulting in uneven dispersion, leading to local cell merging and collapse, deterioration of the cell structure, uneven foaming, and an increased density. The mechanical properties deteriorated most severely, with tensile strength dropping from 13.4 MPa to 8.9 MPa and elongation at break from 9.3% to 4.6%, both reaching the lowest values ​​among all groups. Unencapsulated core powder formed interface defects and stress concentration points in the matrix, severely impairing the strength and toughness of the plate, further demonstrating that the microcapsule encapsulation structure is crucial for achieving a balance between flame retardancy, low density, and mechanical properties.

[0053] It should be noted that the above embodiments are merely some preferred embodiments of the present invention, and not all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

Claims

1. A high flame-retardant, low-density PVC composite foam board, characterized in that, The raw materials include the following parts by weight: 100 parts polyvinyl chloride resin, 1-3 parts foaming agent, 5-15 parts foaming stabilizer, 2-5 parts calcium-zinc composite heat stabilizer, 5-10 parts processing aid, 10-20 parts light calcium carbonate, 0.5-2 parts lubricant, 5-15 parts modified phosphorus-silicon flame retardant microcapsules, and 3-10 parts phytic acid bacteria bran-based porous carbon.

2. The high flame-retardant low-density PVC composite foam board according to claim 1, characterized in that, The preparation method of the modified phosphorus silicon flame retardant microcapsules is as follows: (1) Disperse piperazine pyrophosphate and boric acid in deionized water at a mass ratio of 1:0.3-0.8 to prepare a suspension, stir at 80℃ for 2 hours, and spray dry to obtain core powder; (2) Mix the above core powder with deionized water at a mass ratio of 1:10, then add 2% of Tween-80 by mass of the core powder, and ultrasonically disperse the mixture at room temperature for 30 minutes to form a suspension. Adjust the pH to 8.0-8.

5. (3) Place the system in a 45°C water bath, take 20% of the core powder mass of vinyltriethoxysilane, and add an equal mass of anhydrous ethanol to mix and obtain a mixture. Add the mixture dropwise to the suspension in step 2, stir at a constant temperature for 5.5 h, let stand for 2 h, centrifuge to separate the solid product, wash with deionized water and anhydrous ethanol 2-3 times in sequence, and vacuum dry to constant weight to obtain modified phosphorus silicon flame retardant microcapsules.

3. The high flame-retardant low-density PVC composite foam board according to claim 2, characterized in that, The total mass ratio of piperazine pyrophosphate and boric acid to deionized water is 1:

4.

4. The high flame-retardant low-density PVC composite foam board according to claim 1, characterized in that, The method for preparing the phytic acid-oxidizing bacteria bran-based porous carbon is as follows: S1: The waste mushroom residue was dried and pulverized. The dried mushroom residue powder was weighed according to a mass ratio of 1:2 to solid KOH and a 20wt% KOH aqueous solution was prepared to impregnate the dried mushroom residue powder for 12 hours and then dried. The above mixture was carbonized for 1.5 hours at 800℃ under nitrogen protection at a temperature of 5℃ / min. The product was soaked in 0.1 mol / L hydrochloric acid, washed with deionized water until neutral, and dried to obtain mushroom residue-based porous carbon. S2: Disperse porous carbon in a 15-30wt% phytic acid aqueous solution with a mass-to-volume ratio of 1g:10mL. Stir in a water bath at 60℃ for 4h. After filtering the reaction solution, wash the solid product with deionized water, dry it under vacuum at 80℃, and bake it at 120℃ for 4h to obtain phytic acid-modified bran-based porous carbon.

5. The high flame-retardant low-density PVC composite foam board according to claim 1, characterized in that, The foaming agent is azodicarbonamide and sodium bicarbonate, with a mass ratio of 1:0.

8.

6. The high flame-retardant low-density PVC composite foam board according to claim 1, characterized in that, The foaming stabilizer is an acrylate foaming regulator, and the processing aid is an acrylate copolymer.

7. The high flame-retardant low-density PVC composite foam board according to claim 1, characterized in that, The lubricant is polyethylene wax and stearic acid, with a mass ratio of 1:

1.

8. A preparation process for the high flame-retardant low-density PVC composite foam board according to any one of claims 1-7, characterized in that, Preparation includes the following steps: (1) First, prepare modified phosphorus-silicon flame-retardant microcapsules and phytic acid bacteria bran-based porous carbon. Add the weighed PVC resin, calcium-zinc composite stabilizer, processing aid, foaming stabilizer and lubricant to the mixer and start stirring at 200 rpm. When the material temperature rises to 60-70℃, add light calcium carbonate, modified phosphorus-silicon flame-retardant microcapsules and phytic acid bacteria bran-based porous carbon, and stir at a rate of 400-600 rpm. When the temperature of the mixture rises to 100-110℃, add the pre-mixed foaming agent and stir at a rate of 100 rpm for 1-2 minutes. Discharge the mixture into a cold mixer and stir and cool until the material temperature is <40℃ to obtain a dry powder premix. (2) Add the cooled premixed material into the hopper of the conical twin-screw extruder, and set the temperature of each section of the extruder as follows: feeding section 150-160℃, compression section 160-170℃, metering section 170-180℃, die head temperature 165-175℃, and screw speed controlled at 15-25r / min. (3) The material is plasticized and melted in the extruder. After the melt is extruded through the die, it is cooled and shaped in the shaping device. The board is then pulled and cut to a fixed length to obtain a high flame retardant low density PVC composite foam board.